THE EFFECT OF WORKPLACE BULLYING ON TURNOVER INTENTION, MEDIATING ROLE OF EMPLOYEE RUMINATION, A QUANTITATIVE STUDY OF THREE HOSPITALS LOCATED AT KHYBER PAKHTUNKHWA - Khan, Muhammad Imran; Mehmood, Sultan; Mahnaz, Wajid; Ali, Ejaz; Ahmad, Mubashir (The journal of contemporary issues in business and government, 2022)
The main purpose of this research study is to find the impact of workplace bullying on turnover intentions of the staffs which are the major problems in hospitals and have enormous destructive consequences and rumination increases this phenomenon both ways. This model presents the effect of workplace bullying results on turnover intentions as mediated by employee‟s rumination. The technique applied for the accumulation of data from 270 personnel was convenience sampling technique, for further aid, adopted questionnaires were used which consisted on the measurement of 5 points Likert scale for each variable. To fulfill the criteria of data analysis, reliability, correlation, and regression were used as statistical tools. Results demonstrate that the relationship between Workplace Bullying and turnover intentions is affirmative and noteworthy. As signified by the results employee rumination role was also conciliatory between Workplace Bullying and turnover intentions. Consequently personnel having workplace bullying and also the rumination, their turnover intentions will increase as these factors will increase. The study represents the clear picture of the workplace bullying and its impacts on staffs. Hospital management must take serious actions on such a hostile environment and whatever the circumstances, they must provide the safe and healthy environment for their staffs as their basic requirement to work more positively and voluntarily.